Climate science literacy evaluation of senior high school students: a platform for science curriculum enhancement - Balan, Hazel R.; Bulay, Minie L.; Raganas, Nelia S. (Institute of Advanced Engineering and Science, 2025)
The national achievement test results for grade 12 in Gingoog City Division revealed low science proficiency in critical thinking, information literacy, and problem-solving. This study evaluated science literacy related to climate science among senior high school students, focusing on scientific knowledge, competence, and attitudes as a platform for science curriculum enhancement. A descriptive-comparative design was utilized, involving 339 students from randomly selected public secondary schools, determined through stratified sampling using Slovin’s formula with a .05 margin of error. Three instruments were modified for the study and validated by experts: a 30-item multiple-choice test for scientific knowledge, a 10-item Likert scale for scientific competence, and a 20-item for scientific attitudes. A pilot test with 30 non-participants yielded a Cronbach’s alpha of .76, indicating acceptable reliability. Data analysis involved descriptive and inferential statistics. Results revealed that students in both academic and technical-vocational-livelihood (TVL) tracks generally exhibited low proficiency in scientific knowledge regarding climate change but high scientific competence and attitudes. Significant differences between academic and TVL students in scientific knowledge, competence, and affective engagement were noted. The study concluded that there is a need to improve educational strategies to address learning gaps. Curriculum enhancements should strengthen scientific understanding by integrating climate science topics and developing learning resources and activities.